Struktur, Makna, dan Jenis Takhayul Masyarakat Desa Kesik Kecamatan Masbagik Kabupaten Lombok Timur - Purnawarman Purnawarman; Nurul Hikmah (Jurnal Ilmiah Telaah, 2023)
The  research  entitled  "The  structure,  meaning,  and  types  of  superstitions  of the  people  of  Kesik  Village,  Masbagik  District,  East  Lombok  Regency"  aims  to  preserve  traditional  regional  culture  that  can  enrich  the  nation's cultural  treasures  so  that  they  are  not  extinct  by  the  times  and  advances  in technology.  The  entry  of  foreign  cultures  can  also  affect  the  extinction  of  regional  culture  which  has  become  the  identity  of  the  community  since ancient  times. Data  collection  was  done  by  unstructured  but  focused  interview  method, applying  recording  technique,  note-taking  technique,  and  observation,  all  informants  were  taken  from  the  old  group  and  the  young  group.  Then  the  data  obtained  were  analyzed  using  structural  approach  and  semiotic  theory. Based  on  the  results  of  the  data  analysis,  it  can  be  concluded  that  the superstition  of  Kesik  village  has  icons,  symbols,  indexes,  and  4  kinds  of  structures,  namely:  a)  cause-effect,  b)  cause-effect-conversion,  c)  cause-effect,  d)  effect-conversion.  As  for  the  types,  they are a) superstition about the human life, b) superstition about human body and medicine. d) superstition  about human jobs and social relationship, e) superstition  about traveling, f) superstition about the other live.   Superstition  in  the  Kesik  village  community,  whether  consciously  or  not,  contains  many  teachings  of  educational  values  that  lead  people  to  goodness,  while  the teachings  conveyed  through  their  meaning  are  in  the  form  of  teachings  on how  to  speak  and  behave.